MODEL PEMBELAJARAN MRSA DAN PENGARUHNYA TERHADAP KINERJA PENALARAN MERs DAN KETERAMPILAN PEMODELAN SISTEM KOMPLEKS MAHASISWA - Sumarno Sumarno; Prasetiyo Prasetiyo; Muslimin Ibrahim (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
Structure adaptation is caused by the interaction of plants with the environment, so it requires system thinking in understanding it. This study was conducted to examine the instructional impact of the Multiple Representations Supported Argumentation (MRSA) learning model which involves students doing reasoning using multi representations to facilitate complex system modeling skills. The study was conducted with an iterative design that involves collecting data with MERs reasoning instruments and modeling complex systems. The research involved 1 model lecturer and 3 partner lecturers and 135 students who took part in the structure of plant development. The results of data analysis show the number of students who think complexly with MERs reasoning has increased by 48%, while the number of students who are able to model complex systems with good criteria has increased by 23%. Correlation test results between MERs reasoning performance with complex system modeling in general showed a positive relationship between 0.07 to 0.61. These evidences indicate that instructional learning has an effect on the progress of MERs reasoning performance as well as having an impact on the progress in achieving the ability of modeling complex systems, thus indicating instructional reasoning with MERs is effective for training systems thinking through modeling complex systems.